Am I Entitled to Help? Building Confidence Through Financial Inclusion - Marilla Kortesalmi; Minna Autio; Mette Ranta (Journal of Financial Therapy, 2024)
Financial inclusion has focused primarily on the accessibility of financial social services. However, it is important to note that individual financial practices not only require the opportunity to access financial structures, but also confidence in their accessibility to engage in and utilize such services. Individuals facing difficult life situations often encounter challenges in financial activities due to limited resources and a need for more skills. Consequently, their financial capability is often restricted, and they more frequently experience financial exclusion. Despite this problem, the literature on financial inclusion needs to give more attention to subjective financial inclusion. To understand the process of financially including vulnerable consumers, this study examines how experienced financial inclusion was a crucial element of financial capability in study participants’ daily financial activities. The study collected qualitative data from patients at Addiction Hospital in Järvenpää, Finland. The findings indicate that, before their experienced financial inclusion, the participants felt confident in being entitled to the available financial social services and their achievability. We suggest that supportive financial coaching should not only empower personal abilities and enable external opportunities but also build confidence in a sense of entitlement to fully utilize available financial social services.
Keywords: financial confidence; financial inclusion; financial coaching; vulnerable consumers